Deaf hearing: Implicit discrimination of auditory content in a patient with mixed hearing loss. (17th February 2017) - Brogaard, Berit; Marlow, Kristian; Overgaard, Morten; Schwartz, Bennett L.; Zopluoglu, Cengiz; Tomson, Steffie; Neufed, Janina; Sinke, Christopher; Owen, Christopher; Eagleman, David
Abstract: We describe a patient LS, profoundly deaf in both ears from birth, with underdeveloped superior temporal gyri. Without hearing aids, LS displays no ability to detect sounds below a fixed threshold of 60 dBs, which classifies him as clinically deaf. Under these no-hearing-aid conditions, when presented with a forced-choice paradigm in which he is asked to consciously respond, he is unable to make above-chance judgments about the presence or location of sounds. However, he is able to make above-chance judgments about the content of sounds presented to him under forced-choice conditions. We demonstrated that LS has faint sensations from auditory stimuli, but questionable awareness of auditory content. LS thus has a form of type-2 deaf hearing with respect to auditory content. As in the case of a subject with acquired deafness and deaf hearing reported on a previous occasion, LS's condition of deaf hearing is akin in some respects to type-2 blindsight. As for the case of type 2 blindsight the case indicates that a form of conscious hearing can arise in the absence of a fully developed auditory cortex.